William W. Coblentz papers - Coblentz, William W. (William Weber), 1873-1962.
Correspondence, journal, writings, notebooks, biographical material, financial records, memorabilia, photographs, and other papers relating chiefly to Coblentz's career as a physicist at the National Bureau of Standards. Coblentz kept the journal during a solar eclipse expedition to Sumatra, Indonesia, and his return through Europe in 1926. Writings include annotated copies of Coblentz's Man's Place in a Superphysical World (1954) and From the Life of a Researcher (1951). Subjects include infrared spectroscopy, the application of radiometry to astronomical problems, stellar and planetary radiation, and psychic phenomena. Correspondents include Cleveland Abbe, C. G. Abbot, George Ellery Hale, Dayton Clarence Miller, A. H. Pfund, and Willis Rodney Whitney.
Physicist and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbe, Cleveland, -- 1838-1916 -- Correspondence; Abbot, C. G. -- 1872-1973 -- Correspondence; Hale, George Ellery, -- 1868-1938 -- Correspondence; Miller, Dayton Clarence, -- 1866-1941 -- Correspondence; Pfund, A. H. -- 1879-1949 -- Correspondence; Whitney, Willis Rodney, -- 1868-1958 -- Correspondence; United States. -- National Bureau of Standards; Astronomy; Infrared spectroscopy; Parapsychology; Planets -- Research; Radiation -- Measurement; Radio astronomy; Scientific expeditions -- Sumatra (Indonesia); Solar eclipses; Stars -- Radiation; Europe -- Description and travel; Authors; Physicists